Pengaruh Motivasi Belajar terhadap Hasil Belajar Siswa Setingkat Madrasah Ibtidaiyah - Nur Aniqa Pernaningtik; Didit Darmawan (Universitas Maritim AMNI Semarang, 2024)
This literature study examines the influence of learning motivation on learning outcomes in various elementary schools of the same level. Learning motivation is a dominant factor in achieving learning outcomes. Teaching and learning activities really need motivation. Motivation can function as a driver to achieve good results. A person will do an activity because of motivation in him/herself. High motivation in learning will achieve optimal results. This study applies the literature review method through the analysis of various relevant scientific sources. The results of the study revealed that student learning motivation has a significant influence on student learning outcomes. The influence of motivation has an important role because motivation is very much needed in the learning process of students to support them in acting in order to achieve the learning goals they want to achieve. Teachers are expected to continue to create and maintain an environment that supports student learning motivation in order to achieve maximum learning outcomes.